Performance and structures of the German science system 2022 - Dimity Stephen; Stephan Stahlschmidt (Expertenkommission Forschung und Innovation (EFI), 2022)
This study updates the annual comparative analysis of the performance and structures of the German science system. We use several bibliometric indicators of productivity and academic impact to assess Germany's performance for the period 1995-2020 compared against 22 countries and the EU13, EU14, EU27, and OECD country groups. Having overtaken the USA in 2018 and the Europe Union in 2019, China continues its growth in the international science system, producing nearly a quarter (23.1%) of all Web of Science-indexed publications in 2020. Germany maintained its position as fourth largest producer with 3.9% of global publications, while India's growth narrowed the gap to rank it fifth (3.8%). Germany continued to publish in highly visible journals and received average attention citations in these journals. China further increased both its presence in highly visible journals and impact in these journals beyond the above average levels first achieved in 2017. Taken together, China's improving performance, the rapidly growing contributions from India, and the declining indicator-based performance of historically strong systems such as the USA, Germany, and France, highlight profound structural changes in the global science system.
Keywords: 330